Polymethylmethacrylate-Based Nanocomposites for Denture Base Fabrication: Impact of Nanoparticle Type and Concentration on the Color Change In Vitro - Abdel-Naser M. Emam; Emad A. Azmy; Mohamed Reda Zaki Al-kholy; Mohammed M. Gad; Mohamed Ahmed Helal (Hindawi Limited, 2023)
Background. Although the mechanical behaviors of PMMA were improved with nanoparticles addition, there is a lack of study on the color changes of nanocomposite denture base resin. This study aimed to assess and compare the color of nanocomposite denture base resin modified with different nanoparticles and concentrations. Materials and Methods. Three nanoparticles (zirconium dioxide (ZNP), titanium dioxide (TNP), and silicon dioxide (SNP)) were added to heat-polymerized acrylic resin in 3 and 7 wt% concentrations. A total of 70 acrylic discs (20 × 2 ± 0.03 mm) specimens were prepared while one without addition (control) and three main groups according to nanoparticles and two subgroups according to % (3ZNP, 7ZNP, 3TNP, 7TNP, 3SNP, and 7SNP) with total 70 acrylic discs (n = 10). Spectrophotometer was used for color change (ΔEab) followed by value conversion to National Bureau of Standards units (NBS) to relate the color alterations (ΔEab) to the clinical environment which aids in determining a threshold for clinical acceptance of the color change. ΔEab data were analyzed and compared using one- and two-way ANOVA tests followed by Bonferroni's post hoc test (α = 0.05). Results. Two-way ANOVA showed that filler type (regardless of filler concentration) had a statistically significant effect on mean ΔEab (P<0.001). Filler concentrations (regardless of filler type) showed a significant effect on mean ΔEab while the filler type and concentration interaction showed no significant effect on mean ΔEab (P<0.001). One-way ANOVA in terms of filler types results showed a significant difference between mean ΔEab (P<0.001), where TNP group showed the highest mean ΔEab followed by ZNP and SNP. Pair-wise comparison revealed that 3% concentration showed a significant lower mean ΔEab than 7% concentration (P<0.001). Conclusion. Modification of heat-polymerized denture base resin with ZNP, TNP, or SNP causes clinically unacceptable color change. TNP produced the highest color change followed by ZNP and SNP, and the color change is concentration dependent; the color change increases as the concentration increases.